Mergers and acquisitions - Weston, J. Fred; Weaver, Samuel C. (New York : McGraw-Hill, 2001)
Based on UCLA's executive education mergers and acquisitions program, this concise guide will help professionals needing M&A knowledge understand legal and regulatory environments; how to structure deals from financial, tax, and accounting standpoints; and how to analyze valuation models and use them to gauge the effects of a potential merger.
Includes index.
oif 04/02/15; rua 24/02/15
Loan
Keywords: Consolidation and merger of corporations; Merger and acquisitions; Consolidation and merger of corporations.- Unites states; Takeovers, mergers & buy-outs